PERAN SERTA ORANG TUA DALAM MEMBINA KARAKTER ANAK BERHADAPAN DENGAN HUKUM (ABH) - Endang Switri; Abdul Gofur (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Children are part of their parents' generation, society and also the country. So children play an important role in developing their environment, their families, society and the country. In this way, we need to develop the character of these children so that children do not make mistakes in their steps and when children make mistakes in socializing and are influenced by the surrounding environment, parents of course still strive to ensure that their children's character can be developed to be good or better. Scientific work examines the role of parents in developing character in dealing with the law. This study uses qualitative research using interview data collection tools and carrying out observations. In the study, it is discussed that parents have a role in developing the character of their children starting from an early age, because this child is a trust, entrusted and this child is also a source of comfort for the parents, in fact this child is also a test for the parents.